2018
DOI: 10.1002/jper.17-0575
|View full text |Cite
|
Sign up to set email alerts
|

Influence of plaque control on the relationship between rheumatoid arthritis and periodontal health status among Japanese rheumatoid arthritis patients

Abstract: This study suggests that it is important to consider the influence of plaque control when assessing the relationship between RA severity and periodontal health status in RA patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…There is now increasing evidence that periodontal non-surgical treatment affects the progression of CP and improves the levels of the systemic inflammatory cytokines in patients. 30 Periodontal non-surgical treatment can improve oral hygiene and P. gingivalis counts in patients, which may transiently reduce the disease activity of RA. The data in Table 6 shows significant differences in PD, SBI, IL-6, and CRP before and after the basic periodontal disease therapy, indicating that the treatment had a substantial effect on the oral symptoms and serum indicators in patients.…”
mentioning
confidence: 99%
“…There is now increasing evidence that periodontal non-surgical treatment affects the progression of CP and improves the levels of the systemic inflammatory cytokines in patients. 30 Periodontal non-surgical treatment can improve oral hygiene and P. gingivalis counts in patients, which may transiently reduce the disease activity of RA. The data in Table 6 shows significant differences in PD, SBI, IL-6, and CRP before and after the basic periodontal disease therapy, indicating that the treatment had a substantial effect on the oral symptoms and serum indicators in patients.…”
mentioning
confidence: 99%
“…RA is a risk factor for both caries and periodontal disease [ 3 ]. The plausible link between compromised plaque control and joint dysfunction is reasonable but the contribution of RA to overall inflammatory burden is also an important consideration [ 131 ]. Active SLE patients showed increased dental caries activity including smooth surface caries when compared to inactive SLE.…”
Section: Discussionmentioning
confidence: 99%
“…This cross-sectional study examined different themes pertaining to patients we previously reported on; the methods for evaluating RA and oral health are based on that study. 16 The diagnosis of RA was made by a rheumatologist in a private orthopaedic clinic based on the 1987 revised criteria of the American Rheumatism Association: 17 (1) morning stiffness in and around joints lasting for ≥1 h before maximal improvement; (2) soft tissue swelling of 3 or more joint areas; (3) swelling of the proximal interphalangeal, metacarpophalangeal, or wrist joints; (4) symmetric swelling; (5) rheumatoid nodules; (6) the presence of rheumatoid factor (RF); and (7) radiographic erosion or periarticular osteopenia in the hand or wrist joints. Criteria 1-4 must have been present for ≥6 weeks to be eligible for inclusion.…”
Section: Methodsmentioning
confidence: 99%
“…The methods for assessing RA were based on our previous paper. 16 The Steinbrocker functional classification was applied by a single physician, who was trained in physical function assessment, to categorise the extent of physical disability from class I to IV as follows: (1) complete functional capacity with the ability to carry out all usual duties without handicap; (2) functional capacity adequate to conduct normal activities despite handicap, discomfort or limited mobility in 1 or more joints; (3) functional capacity adequate to perform only a few or none of the duties of one's usual occupation or of self-care; and (4) largely or wholly incapacitated, with the patient bedridden or confined to a wheelchair, permitting little or no self-care. 18 The Steinbrocker stage classification was applied by a single physician to categorise the extent of joint disability from stage I to IV, as follows: I. early: (1) no destructive changes radiographically; (2) radiographic evidence of osteoporosis may be present; II.…”
Section: Methodsmentioning
confidence: 99%